Pengaruh Leverage Ratio terhadap Profitabilitas RoA untuk Mengukur Efektivitas Pengelolaan Aset Pada CV Dua Elang Makmur - Dessy Damayanti; Dedi Junaedi; Ela Nurlaela (Economic Reviews Journal, 2023)
The research method used in this study is a quantitative method. The population in this study is the financial statements of CV. Two Prosperous Eagles for the 2017-2020 period. The sampling technique in this study was carried out by purposive sampling in the form of profit and loss financial statements and balance sheets for the 2017-2020 period. The data used in this research is secondary data. The technique used to analyze the data is descriptive quantitative method with multiple linear regression analysis using IBM SPSS Statistics 21 software. The results of the partial study with the t-test showed that the DAR/DR variable had a negative and insignificant effect on ROA with a tcount of 0.210> 0.05. The results of the partial study with the t-test showed that the DER variable had a negative and insignificant effect on ROA with a tcount of 0.08 > 0.05. The results of the partial study with the t-test showed that the LTDER variable had a positive and significant effect on ROA with a tcount of 0.00 <0.05. While the results of the F test (simultaneous) variables DAR/DR, DER and LTDER have a significant effect on ROA with sig. 0.001 < 0.05, Ftable and Fcount (6.786 > 2.82). Keywords: DAR, DER, LTDER, and ROA.